INFANT MORTALITY SURVEILLANCE SYSTEM, PERNAMBUCO 2013 TO 2022 - Gomes Temoteo Paes, Auta Flavia; Heráclio de Lucena , Isabela (Cadernos ESP, 2025)
Infant mortality remains a significant public health challenge, reflecting social inequalities and weaknesses in maternal and child care. Objective: To evaluate the Infant Mortality Surveillance System in the state of Pernambuco, Brazil, from 2013 to 2022. Methods: This was an evaluative study based on the methodology of the Centers for Disease Control and Prevention, published in 2001, which analyzed data quality through completeness and consistency, as well as the representativeness of the system. The study population included all infant deaths under one year of age recorded between 2013 and 2022. Publicly available data from the Mortality Information System were analyzed using TabNet, Microsoft Excel, and EpiInfo. The study complied with the guidelines of Resolution No. 466, issued in 2012 by the Brazilian National Health Council. Results: During the period, a total of 17,211 infant deaths were recorded. Mean data completeness was 93.8%, classified as excellent, and mean consistency was 99.2%, also classified as excellent. The representativeness of the system was considered good, showing coherence when compared with regional and national databases. Conclusions: The Mortality Information System demonstrated excellent data quality and adequate representativeness. It is recommended that the Ministry of Health promote scientific research on the evaluation of health information systems and that the State Health Secretariat raise awareness among professionals about the importance of accurately completing death certificates, and strengthen Technical Groups and Committees for the Prevention of Infant Deaths.
Keywords: Mortality records; Infant mortality; Health information systems